MODALITY IN BEAUTY AND THE BEAST MOVIE - Weni, Wihelmina A; Separ, Fransiskus M; Kara, Yuliana M D K; Noge, Maria D (Lantern: Journal of Language and Literature, 2024)
This study aimed to find out types and values of modality in Beauty and the Beast movie. In conducting this thesis, the writer used the Systemic Functional Linguistic theory by M.A.K. Halliday (2004), which focused on interpersonal function. This study used descriptive qualitative method. In obtaining the data, the writer took the data from the dialogs, which showing the phrase, clause or utterance that is used in the dialogs of character and writing down the word, phrase, or sentence that are included in the types and values of the modality. The result of this study indicates that there are found 17 utterances containing of modality which is probability, usually, obligation and inclination. Whereas values of modality are divided in three degrees which are high value, medium value, and low value the used by characters in Beauty and the Beast movie.